Korelasi Minat Baca Pustakawan Terhadap Kemajuan Perpustakaan Universitas Negeri Sunan Kalijaga Yogyakarta - Nurfadlliah, Nurfadlliah (STAIN Ponorogo, 2017)
Reading has proven to be an important activity for human being. Hence, a librarian, as an information provider, should have a good reading interest. The research was aimed to examine the correlation between librarians reading interest and the development of Sunan Kalijaga Islamic State University library. The research is of a quantitative one, using the librarians reading interest as an independent variable and the development of the library as a dependent one. The result of the research shows that there is a significant effect of the librarians reading interest toward the development of the university library. The result gives a quite high value of the librarians reading interest and the library development variable by a grand mean of 2,96 and 3.03 consecutively. The simple linear regression experiment using linear regression coefficient provides that Y=29,811 + 0,562X. The constant 29,811 means that if there is no increase in the librarians reading interest, the library development value is 29,811. While regression coefficient 0.562 provides that each increase of the librariansÂ reading interest raises the library development value by 0.562. The research puts recommendation that each librarian should be provided time to read book every day